First documentation of plastic ingestion in the arctic glaucous gull (Larus hyperboreus) - Benjaminsen Stine Charlotte; Bourgeon Sophie; Herzke Dorte; Ask Amalie; Collard France; Gabrielsen Geir Wing (Elsevier, 2022)
Arctic wildlife is facing multiple stressors, including increasing plastic pollution. Seabirds are intrinsic to marine ecosystems, but most seabird populations are declining. We lack knowledge on plastic ingestion in many arctic seabird species, and there is an urgent need for more information to enable risk assessment and monitoring. Our study aimed to investigate the occurrence of plastics in glaucous gulls (Larus hyperboreus) breeding on Svalbard. The glaucous gull is a sentinel species for the health of the arctic marine ecosystem, but there have been no studies investigating plastic occurrence in this species since 1994. As a surface feeder and generalist living in an area with high human activity on Svalbard, we expected to find plastic in its stomach. We investigated for plastic >1 mm and documented plastic ingestion for the first time in glaucous gulls, with a frequency of occurrence of 14.3% (n = 21). The plastics were all identified as user plastics and consisted of polypropylene (PP) and polystyrene (PS). Our study provides new quantitative and qualitative data on plastic burden and polymer type reported in a standardized manner establishing a reference point for future research and monitoring of arctic gulls on national and international levels.